Children’s Story Textbook and Character Education for the Elementary Students - Nazurty, Nazurty; Haryanto, Eddy; Masurai, Puti (Indonesian Research Journal in Education |IRJE|, 2022)
This research aimed to develop textbooks containing short stories for young learners based on character education for the fourth grade students at one elementary school. The research subjects were elementary school students, while the research object was children’s stories. Children’s stories are tales that narrate a story close to the world of children and use language that is easy to be understood by them. The children’s story textbook developed in this research was a literary work that reflects the value of character education. The method used was ResearchÂ and Development. The result was a textbook to teach the fourth-grade students in the state elementary school, which contains children’s story based on character education values. The findings illustrated by the expert validation showed that the textbook was feasible. It was effective since the learning results increased. In the trial, the learning goal was achieved in the time allocated. The textbook fascination was described from the interview result with the teacher and students at the trial. In addition, the student’s responses to learning with the textbook were reflected in their enthusiastic learning behaviors. The assessment conducted by the teacher revealed that the average score was 89%, while the individual trial was 84%, the small trial was 96%, and the field trial was 97%. In conclusion, the childrenâ€™s story textbook book based on character education was considered very interesting, precise, clear, and appropriate.